Characterization and application of cellulose acetate synthesized from sugarcane bagasse - Candido, R. G.; Godoy, G. G.; Gonçalves, Adilson [UNESP] (Elsevier, 2017)
The synthesis and application of cellulose acetate (CA) from sugarcane bagasse were investigated. Firstly, cellulose was extracted by a sequential treatment with H2SO4 (10% v/v), NaOH (5% w/v), EDTA (0.5% w/V), and H2O2 (5% v/v), and characterized by X-ray diffraction (DRX). After the acetylation of the extracted cellulose, CA was characterized using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermogravimetry analysis (TGA), and was applied in the membrane production. The membranes were analyzed by DSC and atomic force microscopy (AFM), and tested in the flux of water vapor to determinate the best conditions for membrane manufacturing. FTIR analysis proved the replacement of free OH groups by acetyl groups, and the thermal analysis showed that sugarcane bagasse CA possessed thermal properties compared to commercial grade CA. The best conditions to prepare membrane were: 3% (w/v) of polymer/solvent relation, 10 min of solvent evaporation time, and 20 °C as temperature for the coagulation bath. These results show that CA can be successfully synthesized from sugarcane bagasse and applied in membrane preparation.
Keywords: Cellulose acetate; Cellulose acetate application; Cellulose derivative; Membrane synthesis; Sugarcane bagasse